Strukturwandlungen afghanischer Mittelpunktsiedlungen unter dem Einfluß ausländischer Infrastrukturprojekte - Wiebe, Dietrich (ERDKUNDE, 1979)
This paper investigates the effects of the American Helmand Project on the trade structure in the town of Lashkargah and the significance of the integrated German development project for trade in the towns of Gardez und Khost in the Paktia Province. These are examined in the context of problems of urban development in Afghanistan. The change in the structure of trade takes place in three phases: In the initial phase traditional and new structures face each other; the traditional ones are suppressed. In a second phase there is stagnation, which is characterised on the one hand by saturation of the market together with an unwillingness and inability for innovation, and on the other hand by a rise in speculative activities, like the tidal increase in the construction of dwellings and business premises, which leaves behind many half-finished ruins. This is followed by a regression phase during which the most active sections of the population leave for Kabul, the capital of the country, for Iran or the Arabian Gulf States, in order to put their acquired skills to good use. The consumer goods which had entered the country as an accompanying feature of the projects, remain in the market; the new production lines become reduced to only a few firms, but remain insigificant for the pattern of trade as a whole. It remains to be seen whether a renewed promotion of the projects cannot produce another take-off phase, which will result in turn in effective long-term phases.